Physiological and Proteomic Insights Into Red and Blue Light-Mediated Enhancement of in vitro Growth in Scrophularia kakudensis—A Potential Medicinal Plant - Manivannan, Abinaya; Soundararajan, Prabhakaran; Park, Yoo Gyeong; Jeong, Byoung Ryong (Frontiers in Plant Science, 2021)
The current study has determined the effect of red and blue lights on the enhancement of growth, antioxidant property, phytochemical contents, and expression of proteins in Scrophularia kakudensis. In vitro-grown shoot tip explants of S. kakudensis were cultured on the plant growth regulator-free Murashige and Skoog (MS) medium and cultured under the conventional cool white fluorescent lamp (control), blue light-emitting diodes (LED) light, or red LED light. After 4 weeks, growth, stomatal ultrastructure, total phenols and flavonoids, activities of antioxidant enzymes, and protein expressions were determined. Interestingly, blue or red LED treatment increased the shoot length, shoot diameter, root length, and biomass on comparison with the control. In addition, the LED treatments enhanced the contents of phytochemicals in the extracts. The red LED treatment significantly elicited the accumulation of flavonoids in comparison with the control. In accordance with the secondary metabolites, the LED treatments modulated the activities of antioxidant enzymes. Moreover, the proteomic insights using two-dimensional gel electrophoresis system revealed the proteins involved in transcription and translation, carbohydrate mechanism, post-translational modification, and stress responses. Taken together, the incorporation of blue or red LED during in vitro propagation of S. kakudensis can be a beneficial way to increase the plant quality and medicinal values of S. kakudensis.